PENGARUH ROLE AMBIGUITY DAN ROLE CONFLICT TERHADAP KOMITMEN INDEPENDENSI AUDITOR INTERNAL - Prasetyo, Angga; Marsono, Marsono (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2011)
This study aims to determine the influence of role conflict (role conflict) against the commitmentof internal auditors’ independence, and know the effect of role ambiguity (role ambiguity) ofthe Internal Auditor independence commitment. Data was collected through primary method byusing a questionnaire. Then performed the data analysis that includes classical assumption test,F test, t test, and analysis of coefficient of determination (R2). To analyze using SPSS softwareversion 16. Based on research result shows that role conflict has a significant negative effect oncommitment to the independence of internal auditors, and role ambiguity (role ambiguity) has asignificant negative effect on commitment to the independence of internal auditors. While basedon simultaneous test (F test), role conflict (role conflict) and role ambiguity (role ambiguity) havean influence on the commitment of internal auditor independence.